TINJAUAN KEKUATAN RANTING BAMBU ORI SEBAGAI KONEKTOR PADA SAMBUNGAN STRUKTUR KUDA-KUDA BAMBU - Desi Putri; Astuti Masdar (FORUM MEKANIKA, 2016)
Bamboo as construction materials can be used in house building, including columns, beams, partitions, horses, bridges as well as a buffer. The strength of a bamboo construction is influenced by the strength of the connections. At the assembly the construction of bamboo as construction of the horses, the connection with the bolt connector and plate make the horses construction of bamboo less economical because the cost of a bamboo construction will be expensive on the connection.The research is conducted experimentally in two phases of testing. In the early phase of research it is conducted preliminary testing which includes physical and mechanical properties testing of bamboo. The second phase at connection do testing compressive strength with a variety of angles namely 00, 450, and 900. The test results show the value of bamboo moisture content and density of each amount of 12.90% and 0.58 g/cm3. The Connection strength of obtained values theoretically are the lowest strength at 900 angle direction of the strength of 769 kg and the highest on the strength direction with angle of 00 amounting to 1732 kg while the value of the connection strength on the direction angle of 450 amounted to 889 kg. The greater the angle of direction of the force then minimize the connection strength.